Method for constructing C-coated Se / SnSe-coated carbon-hydroxide carbide based on polyurethane sponge and application of C-coated Se / SnSe-coated carbon-hydroxide carbide

Through the C@Se/SnSe@PSC material synthesis method based on polyurethane sponge structure, the problems of large volume changes, poor electronic conductivity and slow transmission kinetics in lithium-ion batteries are solved, and the high cycling stability and electrochemical performance of the material are achieved.

CN119591058APending Publication Date: 2025-03-11HUNAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411175710.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-26
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, SnSe and Se materials have large volume changes, poor electronic conductivity and slow transmission kinetics during charging and discharging, resulting in insufficient electrode powdering and electrochemical performance.

Method used

The C@Se/SnSe@PSC material synthesis method based on polyurethane sponge structure was adopted. After ultrasonic dispersion of selenium, tin and polyurethane fiber sponges in ethylene glycol, the nanocomposite material was calcined.

Benefits of technology

The cyclic stability and electrochemical properties of the material are improved, the discharge capacity is 856mAh g-1 after the initial ten cycles, and remains 342mAh g-1 after 10,000 cycles, which significantly improves the specific capacity and structural stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591058A_ABST
    Figure CN119591058A_ABST
Patent Text Reader

Abstract

The invention relates to a method for constructing C (at) Se / SnSe (at) carbon hydroxide carbide based on polyurethane sponge and application of the C (at) Se / SnSe (at) carbon hydroxide carbide based on polyurethane sponge, selenium, tin (C4H11ClO2Sn, butyl tin chloride dihydroxide) polyurethane sponge and ethylene glycol are used as raw materials, and a C (at) Se / SnSe (at) PSC nano composite material is synthesized through ultrasonic dispersion and a subsequent calcination method. Compared with similar products, the product obtained by the method has the advantages that the method is simple, the energy consumption is low, the repeatability is high, the morphology is uniform, the number of active sites is large, lithium ion batteries (LIBs) are good in cycling stability (for the best example, the discharge capacity is 856 mA h g <-1 > (0.1 A g <-1 >) after initial ten cycles under the current density of 10 A g <-1 >, and the discharge capacity is still kept as high as 342 mA h g <-1 > after 10000 cycles. After the current density is reduced to 0.1 A g <-1 >, the discharge capacity is increased to 1432 mA h g <-1 >), and large-scale production of the material is facilitated. The invention develops a novel method for preparing the C-coated Se / SnSe-coated PSC nanostructure based on polyurethane sponge plastic, and provides reference for promoting future development of the technology of applying the plastic to LIBs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a synthesis method of lithium ion battery negative electrode technical materials, and in particular to a synthesis method of a polyurethane sponge-based C@Se / SnSe@PSC (polyurethane sponge carbon) material, belonging to the field of synthesis of lithium ion battery negative electrode technical materials. Background Art

[0002] Recently, tin selenide (SnSe, SnSe 2 ) and selenium have attracted widespread attention. During the discharge / charge process, SnSe exhibits three different mechanisms: insertion, conversion, and alloying. In addition, its appropriate redox potential, high theoretical capacity (847 mAh g for LIBs) -1 , for SIBs it is 780mAh g -1 ) and layered structure with abundant active sites make SnSe a promising alternative for LIBs / SIBs. However, significant volume fluctuations, poor electronic conductivity, and slow transport kinetics during battery operation may lead to electrode pulverization and insufficient electrochemical performance. As a two-dimensional material, SnSe and SnSe 2 With similar characteristics, SnSe and SnSe have larger lithium ion channels, which is beneficial to improve the utilization of materials and thus increase the specific capacity of batteries. 2 A key obstacle for electrodes is the volume change during charge and discharge, which leads to rapid capacity degradation. 2 Research on base materials has mainly focused on mitigating volume changes and improving slow transport kinetics through strategies such as morphology regulation, carbon modification, and heteroatom doping. In addition, selenium (Se) also faces challenges such as severe capacity fading and poor cycling performance due to low Se utilization during charge and discharge cycles and significant volume expansion during lithiation and delithiation (based on Se (4.81 g cm -3 ) and Li 2 Se(2.07gcm -3 ) has a density of about 180%. Various strategies to encapsulate Se in diverse carbon matrices, such as porous carbon, multi-walled carbon nanotubes, and graphene, are widely adopted to improve Se utilization.

[0003] Plastics are materials that generate carbon. They are ubiquitous and pose a wide range of environmental risks. Plastics are widely used in a variety of fields such as packaging, transportation and food processing due to their convenience, durability and economy. Notably, polyethylene (PE), polypropylene (PP), polyethylene terephthalate (PET) and polyurethane embody this versatility. In particular, polyurethane, as a widely used plastic, has become an important source for the manufacture of various plastic products such as sponges, fibers and engineering plastics. This widespread presence makes plastics a viable carbon source for the manufacture of lithium-ion battery materials. Summary of the invention

[0004] The purpose of the present invention is to solve the shortcomings of the prior art and propose a synthesis method for constructing C@Se / SnSe@PSC materials based on polyurethane sponge.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A method for constructing C@Se / SnSe@carbon-hydrogen-oxygen-carbide based on polyurethane sponge, comprising the following steps:

[0007] S1. Dissolving selenium and an organic tin compound in ethylene glycol, and then adding a hydrocarbon hydroxide to obtain a mixed solution, wherein the molar ratio of selenium to the organic tin compound is ≥3:1, and the mass ratio of selenium to the hydrocarbon hydroxide is 98*3-98*7:550;

[0008] S2, dispersing the materials in the mixed solution uniformly to obtain a uniform mixed solution;

[0009] S3, the uniform mixed solution is calcined in an inert gas atmosphere at a temperature of 300-800°C for a period of not less than 4 hours;

[0010] S4. After cooling, the C@Se / SnSe@ hydrocarbon hydroxide is obtained.

[0011] A further improvement is that the hydrocarbon hydroxide is one of polyurethane sponge PS, polyester fabric PF, polyethylene terephthalate plastic bottle PETB, polypropylene mask non-woven fabric PPM, polypropylene fabric PPF, terephthalic acid TA, and 2,6-naphthalene dicarboxylic acid NA; the hydrocarbon hydroxide is one of polyurethane sponge carbide PSC, polyester fabric carbide PFC, polyethylene terephthalate plastic bottle carbide PETBC, polypropylene mask non-woven fabric carbide PPMC, polypropylene fabric carbide PPFC, terephthalic acid carbide TAC and 2,6-naphthalene dicarboxylic acid carbide NAC.

[0012] Further improvement, the carbon-oxygen compound is polyurethane sponge PS, the carbon-oxygen compound is polyurethane sponge carbide PSC; the organic tin compound is butyltin chloride dihydroxide C 4 H 11 C1O 2 Sn.

[0013] As a further improvement, the mass volume ratio of selenium to ethylene glycol is 98:15 mg / ml.

[0014] As a further improvement, in step S2, ultrasonic treatment for 2 hours is performed to evenly disperse the materials in the mixed solution to obtain a uniform mixed solution.

[0015] As a further improvement, the calcination process is to first heat the temperature to 80°C and keep it for 4 hours, then heat the temperature to 180°C and keep it for 4 hours, and then heat the temperature to 300-800°C and calcine for 4 hours.

[0016] Further improvement, the calcination process is to first heat to 80℃ and keep it for 4h, then heat to 180℃ and keep it for 4h, then heat to 300℃ and calcine for 4h, and then heat to 800℃ and calcine for 4h.

[0017] For further improvement, the heating rate is 5℃ / Min.

[0018] A use of C@Se / SnSe@carbon, hydrogen and oxygen carbide, wherein the C@Se / SnSe@carbon, hydrogen and oxygen carbide is as described above, and the C@Se / SnSe@carbon, hydrogen and oxygen carbide is used as a negative electrode material for a battery.

[0019] As a further improvement, C@Se / SnSe@carbon, hydrogen and oxygen carbide are mixed with acetylene black and sodium alginate in a mass ratio of 8:1:1, ground and dispersed in a mixed solvent of water and ethanol, and then evenly coated on copper foil to obtain the battery negative electrode.

[0020] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:

[0021] The present invention uses selenium, tin (C 4 H 11 C1O 2 Sn, butyltin chloride dihydroxide), polyurethane fiber sponge and ethylene glycol were used as raw materials to synthesize C@Se / SnSe(4)@PSC nanocomposite materials by ultrasonic dispersion and subsequent calcination. Compared with similar products, the products obtained by this method are simple, low in energy consumption, high in repeatability, uniform in morphology, with more active sites and good in cycle stability (at a current density of 10A g -1 After the first ten cycles, the discharge capacity is 856 mAh g -1 (0.1Ag -1), and after 10,000 cycles it still maintains up to 342 mAh g -1 The discharge capacity of the -1 After that, the discharge capacity increased to 1432mAh g -1 ), which is conducive to the realization of large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 .C@Se / SnSe@C

[0023] Figure 2 Synthesis process of C@Se / SnSe@PSC

[0024] Figure 3 Polyester and polyurethane sponges. The main component of the green part is polyester fiber, which retains its sheet-like configuration after carbonization. The main component of the yellow part is polyurethane sponge, which changes its morphology after carbonization. In order to introduce active substances (Se / SnSe) into sponge carbon, we chose the polyurethane sponge part of the sponge as the raw material in the experiment.

[0025] Figure 4 X-ray diffraction patterns, including (a) X-ray diffraction patterns of C@Se / SnSe(4)@PSC and C@Se@PSC, and (b) X-ray diffraction patterns of C@SnSe(4)@PETBC, C@SnSe(4)@PFC, and C@SnSe(4)@PSC-300-800.

[0026] Figure 5 XRD patterns, including (a) XRD patterns of C@Se / SnSe(4)@PSC-300, C@Se / SnSe(4)@PSC-700 and C@Se / SnSe(4)@PSC-800; (b) XRD pattern of C@Se / SnSe(X, X=3, 4, 5 and 7)@PSC; XRD patterns of C@SnSe(4)@PPMC, C@SnSe(4)@TAC, C@SnSe(4)@NAC and C@SnSe(4)@PPFC; (d) XRD patterns of PETBC, PPMC, TAC and PPFC; (e) XRD pattern of C@SnSe2@OMWCNT-300; (f) XRD patterns of PSC-300, PSC-700, PSC-800, C@Se@PSC-300, C@Se@PSC-700 and C@Se@PSC-800.

[0027] Figure 6 SEM images, (a, b) C@Se / SnSe(2)@PSC, (c, d)

[0028] C@Se / SnSe(3)@PSC, and (ef)C@Se / SnSe(4)@PSC.

[0029] Figure 7 Scanning electron microscope images: (a, b) C@Se / SnSe(7)@PSC, (c, d)

[0030] C@Se / SnSe(6)@PSC and (e,f)C@Se / SnSe(5)@PSC.

[0031] Figure 8 Scanning electron microscope image 2, including (a, b) PSC-300 and (c, d) PSC-800.

[0032] Fig. 9 Scanning electron microscope images 3, including (a, b) scanning electron microscope images of C@Se@PSC-300, (c, d) scanning electron microscope images of C@Se@PSC-700, and (e, f)

[0033] Scanning electron microscope image of C@Se@PSC-800.

[0034] Fig.10 Four scanning electron microscope images, including (a, b) C@SnSe(4)@PSC-300-800, (c, d) C@SnSe(5)@PSC-300-800 and (e, f) C@SnSe(6)@PSC-300-800.

[0035] Fig.11 Scanning electron microscope images, including (a, b) C@SnSe(7)@PSC-300-800 and (c, d) C@SnSe(8)@PSC-300-800.

[0036] Fig.12 SEM images, including (a, b) C@SnSe(4)@PETBC, (c, d) C@SnSe(4)@PFC and (e, f) C@SnSe(4)@PPMC.

[0037] Fig.13 Scanning electron microscope image 6, where (a, b) C@SnSe(4)@TAC, (c, d)

[0038] Scanning electron microscope images of C@SnSe(4)@NAC and (e, f) C@SnSe(4)@PPFC.

[0039] Fig.14Scanning electron microscope image 7, where (a, b) C@SnSe 2 @OMWCNT-300 and (c, d) C@SnSe 2 Scanning electron microscope image of @OMWCNT-800.

[0040] Fig.15 TEM images, STEM images, element distribution maps and EDS analysis results of C@Se / SnSe(4)@PSC. (a–f) show the TEM images of C@Se / SnSe(4)@PSC, (g) is the STEM image, (h–l) are the corresponding EDS element distribution maps, and (m) is the EDS analysis result of C@Se / SnSe(4)@PSC.

[0041] Fig.16 TEM images, STEM images, and element distribution maps of C@Se / SnSe(7)@PSC. (a–c) show the TEM images of C@Se / SnSe(7)@PSC, (d) is the STEM image, and (e–i) are the corresponding EDS element distribution maps.

[0042] Fig.17 The microscopic image, element distribution diagram and spectral analysis result diagram of C@Se@PSC, among which,

[0043] (ae) Transmission electron microscopy image of C@Se@PSC, (f) high-resolution transmission electron microscopy image, (g) scanning transmission electron microscopy image and the corresponding (hk) energy dispersive X-ray spectroscopy element distribution map, (l) energy dispersive X-ray spectroscopy analysis results of C@Se@PSC.

[0044] Fig.18 TEM, STEM, HRTEM and mapping images of C@SnSe(7)@PSC-300-800; TEM (a, b), HRTEM of C@SnSe(7)@PSC-300-800 and STEM (d) images, and the corresponding (ei) EDS element mapping diagrams.

[0045] Fig.19 Figure 2 shows the Raman frequency shift diagram, XPS analysis result diagram and XPS spectrum diagram. (a, b) show the Raman frequency shift diagrams of C@Se / SnSe(4)@PSC, C@Se@PSC and PSC. (c–f) show the XPS analysis results of C@Se / SnSe(4)@PSC, including High-resolution XPS spectra of C 1s, (d) O 1s, (e) Se 3d, and (f) Sn 3d.

[0046] Fig. 20 XPS analysis and TG analysis diagrams, including (a) XPS analysis of C@Se / SnSe(4)@PSC, (b) TG analysis of C@Se / SnSe(3)@PSC, C@Se / SnSe(4)@PSC and C@Se / SnSe(5)@PSC.

[0047] Fig.21 For electrode performance testing Figure 1 , where (a) Cyclic voltammetry curve of C@Se / SnSe(4)@PSC (0.1 mV s -1 ) and (b) constant current discharge / charge voltage curve (0.1Ag -1 ), Discharge / charge curves of C@Se / SnSe(X, X=2,3 and 4)@PSC, C@Se@PSC and PSC (0.5A g -1 ), (d)

[0048] Rate capacity of C@Se / SnSe(4)@PSC, (e) long-term (5 and 10Ag) -1 )performance.

[0049] Fig. 22 For electrode performance testing Figure 2 , where (a) CV curve of C@Se / SnSe(4)@PSC (0.1 mV s -1 , after 10000 cycles), (b) discharge / charge characteristic curves of C@Se / SnSe(X, X=5, 6 and 7)@PSC (0.5Ag -1 ), Discharge / charge characteristic curves of C@SnSe(X,X=4,5 and 6)@PSC-300-800 (0.5Ag -1 ), (d) discharge / charge characteristic curves of C@Se / SnSe(X, X=2, 3 and 4)@PSC (0.5Ag -1 , used for SIB).

[0050] Fig.23 For electrode performance testing Figure 3 , where (a) Cyclic voltammetry curve of C@Se / SnSe(4)@PSC. (b) Graph of Log(scan rate) and Log(peak current). (d) Pseudocapacitance contribution of C@Se / SnSe(4)@PSC (0.2 and 1.2 mV / s). (e) Pseudocapacitance contribution of C@Se / SnSe(4)@PSC. (f)

[0051] Nyquist plots of C@Se@PSC, C@Se@PSC (after 1000 cycles), C@Se / SnSe(4)@PSC, and C@Se / SnSe(4)@PSC (after 10000 cycles).

[0052] Fig.24 For electrode performance testing Figure 4 , where (a) Nyquist plots of C@Se@PSC, C@Se@PSC (after 1000 cycles), C@Se / SnSe(4)@PSC, and C@Se / SnSe(4)@PSC (after 10000 cycles), (b) Zre(Z real ) vs.ω -1 / 2 .

[0053] Fig.25 Detection of C@Se / SnSe(4)@PSC Figure 1 , where (a–c) are ex situ transmission electron microscopy (TEM) images of C@Se / SnSe(4)@PSC, (d) is a scanning transmission electron microscopy (STEM) image of C@Se / SnSe(4)@PSC, (e–i) are element distribution and element mapping of C@Se / SnSe(4)@PSC, and (j) is the energy dispersive spectrum analysis (EDS) result of C@Se / SnSe(4)@PSC (after 10,000 cycles of charging from an open circuit voltage of 0.001 V to 3 V).

[0054] Fig.26 Detection of C@Se / SnSe(4)@PSC Figure 2 , including (a) in situ transmission electron microscopy image of C@Se / SnSe(4)@PSC, (b–f) element distribution and element mapping of C@Se / SnSe(4)@PSC, and (g) EDS analysis results of OCV from 0.001 to 3 V of C@Se / SnSe(4)@PSC after 10,000 cycles.

[0055] Fig. 27 Detection of C@Se / SnSe(4)@PSC Figure 3 Among them, the ex situ SEM analysis changes of C@Se / SnSe(4)@PSC, (a) after charging from open circuit voltage (OCV) 0.001V to 3.0V; (b) after discharging from OCV 3.0V to 0.001V. DETAILED DESCRIPTION

[0056] The reaction raw materials and catalysts involved in the following examples, unless otherwise specified, are conventional commercially available reagents on the market.

[0057] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0058] All reagents can be easily obtained from well-known commercial channels without further purification. Polyurethane sponge (PS), polyester fabric (PF), polyethylene terephthalate plastic bottle (PETB), polypropylene mask nonwoven fabric (PPM), and polypropylene fabric (PPF) were first washed repeatedly with deionized water and ethanol and then dried.

[0059] In Example 1, PSC, PFC, PETBC, PPMC, PPFC, TAC and NAC materials and their lithium storage performance were studied. The preparation method of the composite material includes the following steps:

[0060] S1. Commercially purchased polyurethane sponge PS (the sponge purchased in this patent contains a polyurethane part and a polyester part. The polyester (green component) of the sponge maintains its flaky structure after carbonization. The yellow part is mainly composed of polyurethane, which undergoes morphological changes during the carbonization process. In order to introduce active substances (Se / SnSe) into the sponge carbon, we selected the yellow polyurethane part as the raw material for the experiment, such as Figure 3 , the following polyurethane sponges in this patent are all yellow parts), PF, PETB, PPM and PPF were first randomly cut into pieces, placed in a corundum ark, and then calcined at 800°C for 4 hours in an argon atmosphere. In addition, terephthalic acid (TA) (CAS: 100-21-0) and 2,6-naphthalene dicarboxylic acid (NA) (CAS: 1141-38-4) were also treated in the same way. The resulting carbonized materials were named PSC, PFC, PETBC, PPMC, PPFC, TAC and NAC. In addition, in order to study the synthesis process of the materials, samples were taken at different temperatures during the synthesis process and marked in the form of "sample name-xx". For example, the polyurethane sponge sample obtained at 300°C was marked as "PSC-300".

[0061] The temperature during the addition process is room temperature, i.e., 20 to 30° C. The composite material is a product of PSC, and its morphology is similar to a sphere. The obtained PSC nanocomposite heterojunction material is mixed with acetylene black and sodium alginate in a mass ratio (8:1:1), ground and dispersed in a mixed solvent of water and ethanol, and then evenly coated on a copper foil as a working electrode.

[0062] In Example 2, a C@Se@PSC composite material is constructed and its lithium storage performance is studied. The preparation method of the composite material includes the following steps:

[0063] S1. Take ethylene glycol (15 mL), selenium (98 mg) and polyurethane sponge (550 mg) and mix them evenly;

[0064] S2. Ultrasonicate the solution for 4 hours to evenly disperse the components.

[0065] S3, taking out the above solution and putting it into a corundum ark, then transferring it to a tube furnace containing Ar atmosphere and calcining it at 80°C, 180°C, and 800°C for 4h, 4h, and 4h, with a heating rate of 5°C@Min;

[0066] S4. After ultrasonic and calcination reactions, selenium in the precursor dispersion is encapsulated in the polyurethane sponge carbon, and finally a C@Se@PSC nanocomposite heterojunction material is generated.

[0067] In S1, the temperature during the addition is room temperature, i.e., 20 to 30°C.

[0068] The composite material is the product C@Se@PSC, in which selenium is dispersed in the few-layer carbon structure on the outer surface of the polyurethane sponge carbon.

[0069] The obtained C@Se@PSC nanocomposite heterojunction material was mixed with acetylene black and sodium alginate in a mass ratio of (8:1:1), ground and dispersed in a mixed solvent of water and ethanol, and then evenly coated on copper foil as a working electrode.

[0070] In Example 3, a method for synthesizing a C@Se / SnSe@PSC material based on polyurethane sponge carbon structure, the preparation method of the composite material comprises the following steps:

[0071] S1. For the synthesis of C@Se / SnSe@PSC, excess selenium is added to the system. Selenium and tin (C 4 H 11 C1O 2 Sn, butyltin chloride dihydroxide, CAS: 13355-96-9) in a molar ratio of 3:1. The specific naming is based on C 4 H11C1O 2 For example, when synthesizing C@Se / SnSe(4)@PSC, ethylene glycol (15 mL), selenium (98 mg (0.3×4=1.2 mol)), C 4 H 11 C1O 2 Sn (98 mg (0.1 × 4 = 0.4 mol)) and polyurethane sponge (550 mg) were uniformly mixed.

[0072] S2, ultrasonically treat the solution for 4 hours, add ethylene glycol (15 mL), selenium (98 mg (0.3×4=1.2 mol)), C 4 H 11C1O 2 Sn (98 mg (0.1×4=0.4 mol)) and polyurethane sponge (550 mg) were uniformly dispersed in a uniform mixture.

[0073] S3, taking out the above solution and putting it into a corundum ark, then transferring it to a tube furnace containing Ar atmosphere and calcining it at 80°C, 180°C, and 800°C for 4h, 4h, and 4h, with a heating rate of 5°C@Min;

[0074] S4. After ultrasonic and calcination reactions, the elements in the precursor dispersion are in situ selenized to SnSe, and the organic components are in situ converted into carbon materials, finally generating C@Se / SnSe(4)@PSC nanocomposite heterojunction materials. In addition, for the synthesis of C@Se / SnSe(X, X = 2, 3, 4, 5, 6, and 7)@PSC, only selenium (0.3×X mol, X = 2, 3, 4, 5, 6, and 7) and C are added. 4 H 11 C1O 2 The amount of Sn (0.1×X mol, X=2, 3, 4, 5, 6, and 7) was varied.

[0075] In S1, the temperature during the addition process is room temperature, i.e., 20 to 30°C;.

[0076] The composite material is a product of C@Se / SnSe@PSC nanomaterial, that is, a structure of polyurethane sponge carbon coated with Se / SnSe.

[0077] The obtained C@Se / SnSe (X, X = 2, 3, 4, 5, 6, and 7)@PSC nano three-layer composite heterojunction material was mixed with acetylene black and sodium alginate in a mass ratio of 8:1:1, ground and dispersed in water and ethanol, and then evenly coated on copper foil as a working electrode.

[0078] In Example 4, a method for synthesizing C@Se / SnSe(4)@PFC, C@Se / SnSe(4)@PETBC, C@Se / SnSe(4)@PPMC, C@Se / SnSe(4)@PPFC, C@Se / SnSe(4)@TAC and C@Se / SnSe(4)@NAC materials is provided. The preparation method of the composite material comprises the following steps:

[0079] S1, ethylene glycol (15 mL), selenium (98 mg (0.3 × 4 = 1.2 mol)), C 4 H 11 C1O 2 Sn (98 mg (0.1 × 4 = 0.4 mol)) and PF, PETB, PPM, PPF, TA and NA (550 mg) were uniformly mixed respectively.

[0080] S2, ultrasonically treat the solution for 4 hours, add ethylene glycol (15 mL), selenium (98 mg (0.3×4=1.2 mol)), C 4 H 11 C1O 2 Sn (98 mg (0.1×4=0.4 mol)) was uniformly mixed and dispersed with PF, PETB, PPM, PPF, TA and NA (550 mg), respectively.

[0081] S3, taking out the above solution and putting it into a corundum ark, then transferring it to a tube furnace containing Ar atmosphere and calcining it at 80°C, 180°C, and 800°C for 4h, 4h, and 4h, with a heating rate of 5°C@Min;

[0082] S4. After ultrasonic and calcination reactions, the elements in the precursor dispersion were in situ selenized to SnSe, and the organic components were in situ converted into carbon materials, ultimately generating C@Se / SnSe(4)@PFC, C@Se / SnSe(4)@PETBC, C@Se / SnSe(4)@PPMC, C@Se / SnSe(4)@PPFC, C@Se / SnSe(4)@TAC and C@Se / SnSe(4)@NAC.

[0083] In Example 5, a method for synthesizing a C@Se / SnSe(4)@PSC-300-800 material is provided. The method for preparing the composite material comprises the following steps:

[0084] S1. For the synthesis of C@Se / SnSe@PSC-300-800, excess selenium was added to the system. Selenium and tin (C 4 H 11 C1O 2 Sn, butyltin chloride dihydroxide, CAS: 13355-96-9) in a molar ratio of 3:1. The specific naming is based on C 4 H11C1O 2 For example, when synthesizing C@Se / SnSe(4)@PSC-300-800, ethylene glycol (15 mL), selenium (98 mg (0.3×4=1.2 mol)), C 4 H 11 C1O 2 Sn (98 mg (0.1 × 4 = 0.4 mol)) and polyurethane sponge (550 mg) were uniformly mixed.

[0085] S2, ultrasonically treat the solution for 4 hours, add ethylene glycol (15 mL), selenium (98 mg (0.3×4=1.2 mol)), C 4 H 11 C1O2 A homogeneous mixture of Sn (98 mg (0.1×4 = 0.4 mol)) and polyurethane sponge (550 mg) was uniformly dispersed.

[0086] S3. The above solution was taken out and placed in a corundum boat, and then transferred to a tubular furnace with an Ar atmosphere and calcined at 80 °C, 180 °C, 300 °C, and 800 °C for 4 h, 4 h, 4 h, and 4 h respectively, with a heating rate of 5 °C / min.

[0087] S4. After ultrasonic treatment and calcination reactions, the elements in the precursor dispersion were in-situ selenized to SnSe, and the organic components were in-situ converted into carbon materials, finally generating a C@Se / SnSe(4)@PSC-300-800 nanocomposite heterojunction material. In addition, for the synthesis of C@Se / SnSe(X, X = 4, 5, 6, and 7)@PSC-300-800, only the amount of selenium added (0.3×X mol, X = 4, 5, 6, and 7) and C 4 H 11 ClO 2 The amount of Sn(0.1×X mol, X = 4, 5, 6, and 7) was different.

[0088] In S1, during the addition process, the temperature was room temperature, i.e., 20 - 30 °C.

[0089] The composite material was a C@Se / SnSe@PSC nanomaterial, that is, a structure of polyurethane sponge carbon-coated Se / SnSe.

[0090] The obtained C@Se / SnSe(X, X = 2, 3, 4, 5, 6, and 7)@PSC nanolayered composite heterojunction material was mixed with acetylene black and sodium alginate in a mass ratio of 8:1:1, ground, and then dispersed in water and ethanol, and then evenly coated on a copper foil to make a working electrode.

[0091] In Example 6, a method for synthesizing a C@SnSe 2 @OMWCNT (oxidized multi-walled carbon nanotubes: OMWCNT) material, and the preparation method of this composite material includes the following steps:

[0092] S1. For the synthesis of C@SnSe 2 @OMWCNT, ethylene glycol (15 mL), OMWCNT (16 mg), selenium (24 mg), and dibutyltin dihydroxide (24.5 mg) were uniformly mixed

[0093] S2. The solution was ultrasonically treated for 4 hours.

[0094] S3, taking out the above solution and putting it into a corundum ark, then transferring it to a tube furnace containing Ar atmosphere and calcining it at 80°C, 180°C, and 800°C for 4h, 4h, 4h, and 4h, with a heating rate of 5°C / min;

[0095] S4. After ultrasonic and calcination reactions, the elements in the precursor dispersion are in situ selenized to SnSe, and the organic components are in situ converted into carbon materials, finally generating C@SnSe 2 @OMWCNT nanocomposite heterojunction material. In addition, in order to study the synthesis process at different temperatures, the material was named "C@SnSe 2 @OMWCNT-xx”.

[0096] The following examples 1-6 are used as representatives for characterization:

[0097] X-ray diffraction analysis is used to characterize the properties of mixed materials. Figure 4 and Figure 5 The X-ray diffraction results shown in the figure show that the Sn metal complex can be selenized to form SnSe at 300°C. From the X-ray diffraction patterns at different temperatures, it can be seen that the relative height of the SnSe peak is the highest at 700°C, while the relative height is the smallest at 800°C, which is significantly lower than the height of the carbon peak at 800°C ( Figure 5 (a) in Figure 1), which indicates that the system may contain substances other than SnSe at 800℃. We speculate that this may be selenium. To verify our hypothesis, we conducted a study on C@Se@PSC( Figure 4 (a)) and PSC( Figure 5 (f) in Figure 1) was subjected to X-ray diffraction tests at different temperatures. X-ray diffraction of the carbonization process of polyurethane sponge at different temperatures (PSC-300, PSC-700 and PSC-800, Figure 5 In (f) of Figure 1, carbonization starts at 300℃, and the relative position of the carbon peak does not change between 700℃ and 800℃, indicating that the carbonization degree reaches a relatively stable state after 700℃. At the same time, among these carbon peaks, the relative height of the carbon peak at 800℃ is the lowest. In the X-ray diffraction peaks at the first two temperatures (300 and 700), PSC-300 and C@Se@PSC-300 ( Figure 5 (f) in), and PSC-700C and @Se@PSC-700( Figure 5 Interestingly, at 800℃, the X-ray diffraction peaks of PSC-800 ( Figure 5 (f)) compared to C@Se@PSC-800( Figure 5 Some new peaks appeared in (f)), mainly corresponding to selenium (JCPDS 38-0768, among which, Figure 5The C@Se@PSC-800 in (f) is Figure 4 This indicates that selenium can be directly embedded in carbonized polyurethane sponge to form a stable composite material, which was also confirmed by subsequent transmission electron microscopy analysis. Combined with the above information, it is shown that at 800°C, the composite system (C@Se / SnSe(4)@PSC-800) may contain not only SnSe but also selenium. The relative peak height of the X-ray diffraction peak of tin selenide also gradually increases with the increase of the tin input ratio (C@Se / SnSe(X, X=3,4,5 and 7)@PSC, Figure 5 (b)), which indicates that the content of active SnSe species in the system can be adjusted by adjusting the feed ratio of tin to carbon, hydrogen and oxygen (polyurethane sponge).

[0098] Usually, composite materials with carbon coating will undergo a selenization process at about 300°C. We also conducted a similar experiment, keeping the sample at 300°C for 4 hours and then heating it to 800°C.

[0099] C(C@Se / SnSe(4)@PSC-300-800, Figure 4 (b) in Figure 2). X-ray diffraction analysis shows that the main product is SnSe, and the relative intensity of the SnSe peak is significantly higher than that of the carbon peak, indicating that SnSe is the main component of the system. This is mainly due to the formation of SnSe as the main product in the 300℃ step.

[0100] Based on the above findings, polyurethane sponge has been confirmed to be able to stably encapsulate directly carbonized tin selenide and selenium. To verify whether similar organic small molecules or polymers can also directly carbonize tin selenide and selenium for encapsulation, we will use other organic small molecules or polymers for encapsulation tests under the same conditions, including PETB, PF, PPM, TA, NA and PPF. The X-ray diffraction peaks of their carbonized materials are similar to those of carbonized polyurethane sponge ( Figure 5 (d) in the figure). However, C@SnSe(4)@PETBC( Figure 4 (b) in), C@SnSe(4)@PFC( Figure 4 (b) in), C@SnSe(4)@PPMC( Figure 5 (c) in), C@SnSe(4)@TAC( Figure 5 (c) in), C@SnSe(4)@NAC( Figure 5 (c)) and C@SnSe(4)@PPFC( Figure 5 The X-ray diffraction pattern of (c)) in FIG. 4 corresponds to SnSe (JCPDS 48-1224), and the height of the X-ray diffraction peak is significantly higher than that of the corresponding carbon peak, indicating that SnSe is mainly present in the system.

[0101] Excess Se input mainly forms SnSe instead of SnSe 2 This may be because carbonization and selenization occur simultaneously when organic molecules or polymers are used as carbon sources, which has an important influence on SnSe 2 The formation of tin selenide (C@SnSe) is unfavorable. We used oxidized multi-walled carbon nanotubes (OMWCNT) as carbon supports and 2 @OMWCNT-300, Figure 5 In (e), X-ray diffraction results confirmed that SnSe 2 The formation of SnSe (JCPDS23-0602) indicates that the use of organic small molecules or polymers as carbon sources has a certain effect on the formation of SnSe, which may provide a reference for the synthesis of SnSe materials.

[0102] PSC, C@Se / SnSe(X)@PSC, C@Se@PSC, C@SnSe(X)@PSC-300-800, C@SnSe(4)@PETBC, C@SnSe(4)@PFC, C@SnSe(4)@PPMC, C@SnSe(4)@TAC, C@SnSe(4)@NAC, C@SnSe(4)@PPFC and

[0103] C@SnSe 2 The morphological characteristics of @OMWCNTs were characterized by SEM technique. Figure 6 and Figure 7 The morphology of C@Se / SnSe(X,X=2,3,4,5,6 and 7)@PSC is shown. From these different Sn input ratios, it can be observed that at smaller ratios, a series of spherical objects grow (C@Se / SnSe(X,X=2 and 3)@PSC), which are likely to be mainly composed of Se / SnSe ( Figure 6 ). The polyurethane sponge carbonized at 800 °C also showed a spherical morphology (PSC, Figure 8 ), while the morphology of C@Se@PSC ( Fig. 9 ) is spherical in shape and covered with a series of objects on the surface, which are likely to be carbon-coated selenium, which was further verified by TEM imaging ( Fig.17 ). The morphology of C@Se@PSC at different temperatures also varies significantly. At 300℃ (C@Se@PSC-300, Fig. 9 In (a) of Figure 1), the presence of spherical structures can be observed under the thick carbon layer. Similarly, pure PSC-300 shows similar features. At 700 °C (C@Se@PSC-700, Fig. 9 ), the spherical surface is covered with a relatively smooth carbon layer, while at 800 °C (C@Se@PSC-800, Fig. 9 ), a spherical surface began to exhibit a series of structures, consistent with the X-ray diffraction results ( Figure 5 ). This indicates that the small amount of introduced tin (C@Se / SnSe(X,X = 2 and 3)@PSC, Figure 3 ) and selenium (C@Se@PSC, Fig. 9 ) did not significantly change the morphology of PSC respectively. With the increase of tin content (C@Se / SnSe(X,X = 4,5,6 and 7)@PSC, Figure 6 , Figure 7 ), various plate-like, block-like or flower-like morphologies appeared (C@Se / SnSe(X,X = 4,5,6 and 7)@PSC, Figure 6 , Figure 7 ). These surfaces showed a series of particles, as observed by X-ray diffraction. The main component of these large block-like, plate-like or flower-like morphologies was still PSC. This indicates that the increase in tin content did affect the morphology of PSC. These changes promoted the better incorporation of Se / SnSe into PSC. The stable embedding within PSC enhanced their cycling stability as lithium-ion battery electrode materials.

[0104] Interestingly, in this sample (C@SnSe(X,X = 4,5,6,7 and 8)@PSC-300-800, Fig.10 and 11 ), after holding at 300 °C for 4 hours and then at 800 °C for 4 hours, the morphology presented a spherical shape with a layered SnSe structure on the surface, which was further verified by TEM imaging ( Fig.18 ). In addition, through the morphology of composites formed by carbonization of other organic polymers and organic small molecules (C@SnSe(4)@PETBC, C@SnSe(4)@PFC, C@SnSe(4)@PPMC, C@SnSe(4)@TAC, C@SnSe(4)@NAC and C@SnSe(4)@PPFC, Fig.12 and Fig.13 ), it showed the growth of layered SnSe surrounding the blocky carbon surface. For C@SnSe 2 @OMWCNT, the SnSe 2 compound surrounded the OMWCNT during growth, and with the increase of temperature, the thickness of the SnSe 2 layer on the carbon surface decreased significantly. The plate-like morphology of SnSe 2 at 800 °C (C@SnSe 2 @OMWCNT-800, Fig.14 ) was significantly smaller than that at 300 °C (C@SnSe 2 @OMWCNT-300, Fig. 9 ). Fig.15 , Fig.16 , Fig.17 and Fig.18 Transmission electron microscopy (TEM) images of C@Se / SnSe(4)@PSC, C@Se / SnSe(7)@PSC, C@Se@PSC, and C@SnSe(4)@PSC-300-800 are shown. As the tin content increases, the effect on the polyurethane sponge-like carbon morphology becomes more and more obvious. This effect is not found in C@Se / SnSe(4)@PSC( Fig.15 ) and C@Se / SnSe(7)@PSC( Fig.16 ) can be clearly observed in the TEM image that PSC completely encapsulates Se / SnSe to form a stable coating. As the ratio increases, the relative volume of the SnSe layer tends to increase significantly (C@Se / SnSe(7)@PSC, Fig.16 ), which is consistent with the XRD pattern ( Figure 5 For C@Se@PSC and C@SnSe(4)@PSC-300-800, the growth of Se and SnSe around the PSC spheres is consistent with the scanning electron microscopy (SEM) observations.

[0105] Fig.15 The transmission electron microscopy (TEM) images of C@Se / SnSe(4)@PSC are shown. Fig.15 (a)–(f) Fig.16 Medium (g), Fig.15 (h)–(l) and Fig.16 (m) shows the TEM and STEM images and the corresponding EDS element distribution maps (distribution of C, O, Se and Sn in C@Se / SnSe(4)@PSC) and the EDS analysis results of C@Se / SnSe(4)@PSC, respectively. Fig.15 (a)–(f) show the growth of Se / SnSe closely integrated with PSC, especially in Fig.15 This is well demonstrated in (c), (e) and (f). Fig.15 In (c), PSC-coated Se nanoparticles with a diameter of about 10 nm appeared. Similarly, PSC-coated Se nanoparticles with a diameter of about 2 to 4 nm appeared in C@Se@PSC. Fig.17 In (f). Fig.15 (e) and (f) show that the spacing between the (200) and (004) planes of SnSe in C@Se / SnSe(4)@PSC is about 0.58 and 0.3 nm, respectively. Fig.15 In (f), SnSe and Se nanoparticles appear simultaneously and are in contact with each other. Fig.15STEM image of (g) and the corresponding Fig.15 The EDS element distribution diagrams of C@Se / SnSe(4)@PSC in (h)–(l) show that Se and Sn are uniformly distributed in PSC. EDS analysis shows that the atomic ratio of Se to Sn is 3.4 to 1.1, indicating that Se is in excess relative to Sn. Combined with the XRD results ( Figure 4 and Figure 5 , SnSe, JCPDS 48-1224), it can be inferred that Se and SnSe coexist and are dispersed with each other. The results show that PSC successfully encapsulates Se / SnSe, and they exist in the form of mutual dispersion and contact. This helps prevent aggregation and enables them to exist on a small nanoscale. The smaller the size, the higher the relative activity, which is beneficial to increase the energy storage active sites of lithium-ion batteries, thereby improving the specific capacity of the battery.

[0106] Compared with C@Se / SnSe(4)@PSC, in C@Se / SnSe(7)@PSC, SnSe mainly exists in the form of flakes ( Fig.16 In (a)–(c)), the spacing between the (200) planes is about 0.58 nm ( Fig.16 (c)), while the proportion of dispersed nanoparticles is significantly lower ( Fig.16 STEM image of (d) and the corresponding Fig.16 EDS element distribution diagrams of (e)–(i) in Figure 3). For C@Se@PSC and C@SnSe(4)@PSC-300-800, they are distributed on the surface of the PSC spheres ( Fig.17 and Fig.18 ), SnSe mainly exists in the form of flakes, and the spacing between the (200) crystal planes is about 0.58 nm ( Fig.17 (c) in Figure 2). Among these morphologies, C@Se / SnSe(4)@PSC exhibits coexistence of Se and SnSe and complete integration with PSC, while uniformly dispersed nanoparticles. This helps to improve the utilization efficiency of active sites and the cycling stability of the material as an electrode material for lithium-ion batteries.

[0107] Raman analysis has been performed on the characteristics of C@Se / SnSe(4)@PSC, C@Se@PSC and PSC. For C@Se / SnSe(4)@PSC and C@Se@PSC, the atomic vibrations of SnSe and Se should be around 71 cm -1 (A 1 g )、102cm -1 (B 3g ) and 152cm -1 (A 3 g) was observed, but compared with pure PSC, it was not actually detected (see Fig.19 Combined with the previous SEM ( Figure 6 ) and TEM( Fig.15 ) analysis, which indirectly indicates that Se / SnSe are fully encapsulated by the PSC matrix.

[0108] In the Raman spectra of C@Se / SnSe(4)@PSC (1.16), C@Se@PSC (1.2), and PSC (1.19), the ratios from D to G are almost the same, confirming that the defects in the composite PSCs are the same after carbonization. -1 and 1597cm -1 The D and G bands of PSC (see Fig.19 The results show that the introduction of Se and SnSe has no effect on the defect density of PSCs.

[0109] Fig.19 (c)-(f) and Fig. 20 (a) shows the XPS spectrum of C@Se / SnSe(4)@PSC (C, O, Se and Sn). As for the C1s peak ( Fig.19 In (c)), 284.8 eV, 286.2 eV, 287.8 eV and 289.8 eV correspond to C=C, CO, C=O and C-Se bonds, respectively. Figure 7 (d) in Figure 5 shows that 531.2 eV, 533.1 eV and 535.1 eV correspond to C=O, CO and OC=O bonds, respectively. For Se 3d, 53.8 eV and 55.1 eV correspond to Se 3d 5 / 2 and Se 3d 3 / 2 Signal( Figure 7 For Sn 3d, 486.9 eV and 495.3 eV correspond to Sn 3d 5 / 2 and Sn 3d 3 / 2 Signal( Fig.19 (g) in the figure.

[0110] By thermogravimetric analysis (TGA) ( Fig. 20), the Se / SnSe contents in C@Se / SnSe(3)@PSC, C@Se / SnSe(4)@PSC and C@Se / SnSe(5)@PSC were determined. In C@Se / SnSe(3)@PSC, C@Se / SnSe(4)@PSC and C@Se / SnSe(5)@PSC, since selenium is completely wrapped by porous carbon, selenium can only be exposed to air and oxidized / sublimated when PSC begins to oxidize. Therefore, at 400-600°C, Se in Se / SnSe is oxidized / sublimated, while carbon is oxidized. In addition, Sn in SnSe is oxidized to SnO 2 During the thermogravimetric analysis, the complete oxidation of SnSe to SnO 2 , resulting in almost no change in mass after 600°C. The significant change in mass in the system mainly comes from the oxidation of carbon, Se, and Se in SnSe. According to the conservation of Sn elements, the following equations (Equations S1 and S2) are obtained,

[0111]

[0112] M SnSe and Represent SnSe and SnO respectively 2 The average molecular weight, M SnSe %and % represent SnSe and SnO in the system respectively 2 The content percentage of M SnSe =197.67,

[0113]

[0114] Among them, M Sn and Represent Sn and SnO respectively 2 The average molecular weight, m Sn %and % represent Sn and SnO in the system respectively 2 The content percentage of M Sn =118.71,

[0115] % in C@Se / SnSe(3)@PSC, C@Se / SnSe(4)@PSC and C@Se / SnSe(5)@PSC are 14%, 15% and 17%, respectively. Therefore, according to Eq. S1, the corresponding SnSe mass loadings are estimated to be 18.3%, 19.6% and 22.3%. % in C@Se / SnSe(4)@PSC is 15%. Therefore, according to Eq. S2, the corresponding Sn mass loading is estimated to be 11.8%. Then, according to transmission electron microscopy (TEM) (M Sn :M Se =1.02:2.17,M Sn and M Se represent the mass fraction percentage of Sn and Se in C@Se / SnSe(4)@PSC, Fig.15 As shown in m in the figure, the Se content in C@Se / SnSe(4)@PSC is 25.1%. Therefore, the total ratio of Se / SnSe in C@Se / SnSe(4)@PSC is 36.9%, of which the percentages of tin selenide and selenium are 19.6% and 17.3%, respectively.

[0116] The electrochemical performances of PSC, C@Se@PSC, C@Se / SnSe(X)@PSC and C@Se / SnSe(X)@PSC-300-800 were tested using half-cells. Fig.21 (a) shows the cyclic voltammetry (CV) curve of C@Se / SnSe(4)@PSC as a lithium-ion battery anode. In the first CV scan, three peaks (1.62, 0.78, and 0.32 V) appeared during the discharge process. The 1.62 V peak is due to the conversion of metalloid selenium to Li 2 Se, the sharp peak at 0.78 V can be attributed to the x SnSe to Li 2 The small peak at about 0.32 V can be identified as the conversion reaction between Se and metallic tin to form Li x The multi-step alloying process of Sn alloy is accompanied by the irreversible decomposition of electrolyte to form a solid electrolyte interface (SEI) film.

[0117] Fig.21 (b) shows the constant current charge-discharge curves of C@Se / SnSe(4)@PSC (at 0.1A g -1 The first specific capacity of C@Se / SnSe(4)@PSC is 2105 mAh g -1 , charging 829mAh g -1 The initial energy utilization efficiency is only 39%, which is far lower than the 90% to 94% efficiency of industrial graphite negative electrode.

[0118] The main reason for the low initial charge and discharge efficiency of C@Se / SnSe(4)@PSC is that during this process, the electrolyte decomposes at the negative electrode interface to form a SEI film. Fig. 22 (b) in the CV scan ( Fig.21In (a), an oxidation peak in the range of about 0.27 to 2.05 V is observed, which can be attributed to the oxidation of Li x Sn alloy and Li 2 SnSe and Se recombined in Se. Fig. 22 (a) shows the CV scan curve of C@Se / SnSe(4)@PSC after 10,000 cycles of charge and discharge. It can be clearly seen that the peak height is relatively reduced, indicating that with the extension of the cycle period, stable substances are formed on the surface of the material to further encapsulate the active substances, which is beneficial to improve the cyclic stability of the material.

[0119] C@Se / SnSe(X, X=2, 3 and 4)@PSCs exhibited stable capacities of 409, 400 and 551 mAh g after 1000 cycles, respectively. -1 (See Fig.21 (c)). C@Se / SnSe(X, X=5, 6 and 7)@PSCs exhibit stable capacities of 491, 470 and 328 mAh g after 800 cycles, respectively. -1 (See Fig. 22 C@Se@PSC and PSC exhibit stable capacities of 410 and 206 mAh g after 1000 and 500 cycles, respectively. -1 (See Fig.21 (c) in Figure 1). This shows that the battery performance is the best when X = 4. In addition, compared with the simple selenium battery, which releases a capacity that gradually increases from low to high, the introduction of SnSe can increase the battery capacity and improve the battery stability. C@SnSe(X, X = 4, 5 and 6)@PSC-300-800 showed stable capacities of 283, 338 and 334 mAh g after 1000 cycles. -1 (See Fig. 22 (c)). Compared with the previous one, the capacity is obviously lower, indicating that the presence of Se is beneficial to improve the specific capacity of the composite system compared with pure SnSe. C@Se / SnSe(X, X=2, 3 and 4)@PSC showed stable capacities of 181, 196 and 191 mAh g after 300 cycles, respectively. -1 ( Fig. 22 (d)) for sodium-ion batteries. C@Se@PSC exhibits a stable capacity of 101 mAh g after 300 cycles. -1 ( Fig. 22 (d) in the figure is used for sodium-ion batteries. The battery capacity does not change significantly, indicating that the atomic radius of sodium ions is larger than that of lithium ions, which is not conducive to their embedding into the active material (Se / SnSe). The measured battery capacity should be mainly contributed by the carbon therein. This shows that this system is mainly suitable for lithium-ion battery systems.

[0120] Fig.21 (d) shows the rate performance of C@Se / SnSe(4)@PSC. Specifically, the rate performance of C@Se / SnSe(4)@PSC is improved at 0.1, 0.2, 0.4, 0.8, 1.0, 1.5, 2.0, 3.0, 4.0, 5.0, 10.0, 20.0, and 30.0 A g -1 At current densities of 907, 790, 700, 612, 586, 539, 509, 461, 429, 400, 318, 238 and 190 mAh g -1 The current density was then switched back to 0.1 A g -1 , the discharge capacity is 943mAh g -1 , indicating that C@Se / SnSe(4)@PSC has good reversibility. In particular, Fig.21 (e) shows the C@Se / SnSe(4)@PSC at 5 and 10 A g -1 Long cycle performance at current density. For 5A g -1 The current density (the first ten cycles were at 0.1A g -1 826mAh g -1 ), the discharge capacity of C@Se / SnSe(4)@PSC is still as high as 437 mAh g after 10000 cycles. -1 For 10A g -1 The current density (the first ten cycles were at 0.1A g -1 856mAh g -1 ), the discharge capacity of C@Se / SnSe(4)@PSC is still as high as 342 mAh g after 10000 cycles. -1 Then the current density was switched back to 0.1Ag -1 , discharge capacity is 1432mAh g -1 The results show that polyurethane sponge carbon successfully encapsulates Se / SnSe, and the system exhibits good cycle stability. It has good structural stability under high current, and polyurethane sponge carbon successfully alleviates the volume expansion problem of active substances.

[0121] The capacitance contribution of C@Se / SnSe(4)@PSC was calculated based on the CV data. Fig.23 a shows the cyclic voltammetry curves of various samples.

[0122] i = av b (1)

[0123] log(i) = log(a) + b * log(v) (2)

[0124] Fig.23(b) in Figure 2 shows that at the peak, the values ​​of the C@Se / SnSe(4)@PSC composite are 0.98, 0.58, and 0.72, which are close to 1, corresponding to surface control (capacitance). Specifically, the capacitance contribution ratio of C@Se / SnSe(4)@PSC can be analyzed by equation (3):

[0125] i (v) = k 1 v + k 2 v 0.5 (3)

[0126] Among them, k 1 and k2 are curve iv -0.5 and v 0.5 The appropriate values ​​of the slope and intercept of . k in equation (3) 1 v and k 2 v 0.5 denote the fractions of surface and diffusion controlled behavior, respectively. Fig.23 (c) and (d) show that the capacitance contribution of C@Se / SnSe(4)@PSC is positively correlated with the scan rate, reaching up to 64% and 81% at scan rates of 0.2mV / s and 1.2mV / s, respectively. Fig.23 (e) shows that the pseudocapacitive contribution ratios of C@Se / SnSe(4)@PSC are 64%, 70%, 74%, 77%, 79% and 81%, respectively, at scan rates of 0.2, 0.4, 0.6, 0.8, 1.0 and 1.2 mV / s, which means that the pseudocapacitive contribution of C@Se / SnSe(4)@PSC plays an important role when the nanomaterial is used as a negative electrode for SIBs.

[0127] The electrochemical behaviors of C@Se@PSC, C@Se@PSC (after 1000 cycles), C@Se / SnSe(4)@PSC, and C@Se / SnSe(4)@PSC (after 10000 cycles) were analyzed by electrochemical impedance spectroscopy (EIS). Fig.23 (f) in the figure). The Nyquist plot of the nanomaterial includes a high-frequency semicircle, which corresponds to the charge transfer resistance (Rct) between the electrode and the electrolyte. For C@Se@PSC, C@Se@PSC (after 1000 cycles), C@Se / SnSe(4)@PSC and C@Se / SnSe(4)@PSC (after 10000 cycles), the Rct in the high-frequency band is 72, 48, 58 and 20Ω, respectively. This means that the addition of SnSe and PSC can enhance the charge transfer impedance, improve the conductivity and promote the reaction kinetics of C@Se@PSC and C@Se / SnSe(4)@PSC.

[0128] Fig.24The Nyquist plots of C@Se@PSC, C@Se@PSC (after 1000 cycles), C@Se / SnSe(4)@PSC, and C@Se / SnSe(4)@PSC (after 10000 cycles) are shown. + The diffusion is based on:

[0129] D=R 2 T 2 / 2A 2 n 4 F 4 C 2 σ 2 (6)

[0130] Where R is the gas constant, T is the absolute temperature, A is the surface area of ​​C@Se@PSC, C@Se@PSC (after 1000 cycles), C@Se / SnSe(4)@PSC and C@Se / SnSe(4)@PSC (after 10000 cycles). n is the number of electrons in the charge and discharge process, F is the Faraday constant, and C is the Li + The concentration of σ is obtained by calculation

[25] :

[0131] Z real =R e +R ct +σω -1 / 2 (7)

[0132] R e ,R ct and ω represent resistance, charge impedance, and angular frequency, respectively. Fig.24 (b) shows Z real vs.ω -1 / 2 The fitting results are shown in Figure 2, and σ is determined from the slope. The σ of C@Se@PSC, C@Se@PSC (after 1,000 cycles), C@Se / SnSe(4)@PSC, and C@Se / SnSe(4)@PSC (after 10,000 cycles) are 3757, 1885, 2543, and 582, respectively. The diffusion coefficients (D) of C@Se@PSC, C@Se@PSC (after 1,000 cycles), C@Se / SnSe(4)@PSC, and C@Se / SnSe(4)@PSC (after 10,000 cycles) were then determined. This means that the Li + The mobility of C@Se / SnSe(4)@PSC is higher than that of C@Se@PSC, especially after running 10,000 times, the mobility of C@Se / SnSe(4)@PSC is also higher than that of C@Se@PS, indicating that the introduction of SnSe is beneficial to improve the Li +Mobility, improving battery performance. This is one of the excellent properties of @Se / SnSe(4)@PSC as a negative electrode for lithium-ion batteries.

[0133] To gain deeper insight into the sodium storage mechanism, we employed ex situ measurements at different discharge / charge voltage stages of the initial sodiumation / desodiumation cycles. Figure 25 to Figure 26 As shown in the figure, we selected the typical state after the open circuit voltage (OCV) was charged from 0.01V to 3.0V (after 10,000 charge and discharge cycles) to clarify the evolution process by ex situ transmission electron microscopy (TEM), high resolution transmission electron microscopy (HRTEM) and scanning transmission electron microscopy (STEM). After charging to 3.0V, the diffraction peak of SnSe can be detected, and an obvious Se signal appears at the same time, indicating the reversible reaction of SnSe ( Fig.25 In the STEM image, it can be clearly observed that the system is completely encapsulated in the polyurethane sponge carbon ( Fig.25 (e) and (f)), while Se is concentrated in the middle of Sn ( Fig.25 (h) and (i) in the figure), and Se and Sn are also distributed alternately, indicating that Se and SnSe coexist throughout the entire cycle. From the atomic ratio, Se (2.91) is more than Sn (1.36), which also supports this conclusion. In particular, the focus shot of Se in the middle ( Fig.26 In the results of (g)), Se (12.63) is much higher than Sn (1.43). Fig. 27 (a) and (b) show that the volume expansion rate of the system at the replay point is small, about 15%, indicating that carbon successfully alleviates the volume expansion problem of the active material. Under the joint action of sponge carbon, Se and SnSe, the battery capacity of the composite system and the cycle stability of battery charge and discharge are improved.

[0134] In summary, the C@Se / SnSe(4)@PSC nanostructure was successfully synthesized in one step based on polyurethane sponge and in situ synthesis of SnSe using tin-based organic complexes. Transmission electron microscopy images directly proved the successful synthesis of C@Se / SnSe(4)@PSC. The material was -1 Under the conditions (the initial current density of 10 cycles was 0.1Ag -1 , capacity is 826mAh g -1 ) showed good cycling stability, with a capacity of 437 mAh g after 10,000 cycles. -1 At a current density of 10Ag -1 Under the conditions (the initial current density of 10 cycles was 0.1Ag -1 , capacity is 856mAh g -1), after 10,000 cycles, the capacity is still as high as 342 mAh g -1 . Adjust the current density back to 0.1A -1 After that, the capacity reaches 1432mAh g -1 The non-in-situ results after long cycles showed that the polyurethane sponge carbon successfully encapsulated Se / SnSe in it, and the system showed good structural stability and cycle stability. The polyurethane sponge carbon successfully alleviated the volume expansion problem of the active material.

[0135] The new method of C@Se / SnSe(4)@PSC nanostructure provides a possibility for the high-value utilization of polyurethane in plastics.

Claims

1. A method for constructing C@Se / SnSe@carbon-hydrogen-oxygen-carbide based on polyurethane sponge, characterized in that: The following steps are involved: S1. Dissolving selenium and an organic tin compound in ethylene glycol, and then adding a hydrocarbon hydroxide to obtain a mixed solution, wherein the molar ratio of selenium to the organic tin compound is ≥3:1, and the mass ratio of selenium to the hydrocarbon hydroxide is 98*3-98*7:550; S2, dispersing the materials in the mixed solution uniformly to obtain a uniform mixed solution; S3, the uniform mixed solution is calcined in an inert gas atmosphere at a temperature of 300-800°C for a period of not less than 4 hours; S4. After cooling, the C@Se / SnSe@ hydrocarbon hydroxide is obtained.

2. The method for constructing C@Se / SnSe@ hydrocarbon hydroxide based on polyurethane sponge according to claim 1, characterized in that: The hydrocarbon hydroxide is one of polyurethane sponge PS, polyester fabric PF, polyethylene terephthalate plastic bottle PETB, polypropylene mask non-woven fabric PPM, polypropylene fabric PPF, terephthalic acid TA, and 2,6-naphthalene dicarboxylic acid NA; the hydrocarbon hydroxide is one of polyurethane sponge carbide PSC, polyester fabric carbide PFC, polyethylene terephthalate plastic bottle carbide PETBC, polypropylene mask non-woven fabric carbide PPMC, polypropylene fabric carbide PPFC, terephthalic acid carbide TAC, and 2,6-naphthalene dicarboxylic acid carbide NAC.

3. The method for constructing C@Se / SnSe@ hydrocarbon hydroxide based on polyurethane sponge according to claim 2, characterized in that: The carbon-oxygen compound is polyurethane sponge PS, the carbon-oxygen compound is polyurethane sponge carbide PSC; the organic tin compound is butyltin chloride dihydroxide C4H 11 ClO2Sn.

4. The method for constructing C@Se / SnSe@ hydrocarbon hydroxide based on polyurethane sponge according to claim 1, characterized in that: The mass volume ratio of selenium to ethylene glycol is 98:15 mg / ml.

5. The method for constructing C@Se / SnSe@ hydrocarbon hydroxide based on polyurethane sponge according to claim 1, characterized in that: In step S2, the materials in the mixed solution are evenly dispersed by ultrasonic treatment for 2 hours to obtain a uniform mixed solution.

6. The method for constructing C@Se / SnSe@ hydrocarbon hydroxide based on polyurethane sponge according to claim 1, characterized in that: The calcination process is to first heat to 80°C and keep it for 4 hours, then heat to 180°C and keep it for 4 hours, and then heat to 300-800°C and calcine for 4 hours.

7. The method for constructing C@Se / SnSe@ hydrocarbon hydroxide based on polyurethane sponge according to claim 1, characterized in that: The calcination process is to first heat to 80°C and keep it for 4 hours, then heat to 180°C and keep it for 4 hours, then heat to 300°C and calcine for 4 hours, and then heat to 800°C and calcine for 4 hours.

8. The method for constructing C@Se / SnSe@ hydrocarbon hydroxide based on polyurethane sponge according to claim 6 or 7, characterized in that: The heating rate is 5℃ / Min.

9. A use of C@Se / SnSe@carbon-hydrogen-oxycarbide, characterized in that: The C@Se / SnSe@carbon-hydrogen-oxygen-carbide is as described in any one of claims 1-8, and the C@Se / SnSe@carbon-hydrogen-oxygen-carbide is used as a negative electrode material for a battery.

10. The use of C@Se / SnSe@carbon-hydrogen-oxycarbide as claimed in claim 9, characterized in that: C@Se / SnSe@carbon, hydrogen and oxygen carbide are mixed with acetylene black and sodium alginate in a mass ratio of 8:1:1, ground and dispersed in a mixed solvent of water and ethanol, and then evenly coated on a copper foil to obtain a battery negative electrode.